Chicken Menu Sales Forecasting System using Multiplicative Holt-Winters Triple Exponential Smoothing - Fajar Rohman Hariri; Johan Ericka Wahyu Prakasa (Department of Informatics Engineering, 2023)
Forecasting is an art and a science predict events that will occur in the future based on data in the past. The ability of the restaurant in Management shows success in taking advantage of business opportunities optimal for interpreting past performance and planning for the future. This research uses Triple HoltWinters Exponential Smoothing Multiplicative method for sales forecasting. Multiplicative Holt-Winters Triple Exponential Smoothing Method has the smallest percentage error (PE) of 9.946% with parameter values (α=0.1, β=0.1, ϒ=0.3). While the largest percentage error (PE) is obtained Multiplicative models with parameter values (α=0.3, β=0.3, ϒ=0.1) produce percentage error (PE) value of 11.879%. Menu sales forecasting results chickens using the Holt-Winters Triple Exponential Smoothing Method Multiplicative in the next month using parameter values (α=0.1, β=0.1, ϒ=0.3) is 4782 pcs.